(untitled) (Journal of Rangpur Medical College, 2025)
Background: Medical college teachers now not only provide information but also guide students to validate and identify key issues relevant to their future practice. However, a shortage of teachers in basic medical science subjects is a significant problem, impacting students and the entire medical education system. Objective: This study aimed to assess the effects of teacher shortage in basic subjects on medical education in medical colleges in Bangladesh. Methods: This descriptive cross-sectional study, conducted from January to December 2021 in four medical colleges (two government and two private) in Bangladesh, included 456 subjects. Of these, 96 were basic subject teachers in medical colleges, and 360 were students in the 1st to 3rd phases of the MBBS course. Descriptive statistics and SPSS version 22.0 were utilized for data analysis. Results: In this study, all teachers (100%) and 82.22% of students expressed concerns about a shortage of teachers in their medical colleges. A significant portion of students (29.1%) believed that the shortage of teachers hindered the delivery of sufficient knowledge. Additionally, 23.05% of students reported disruptions in regular and practical classes due to the shortage of teaching staff. Among the 360 students, various suggestions were proposed, with 55.5% advocating for the appointment of more teachers in each basic subject, and 20.28% suggesting increased facilities for basic subject teachers. Conclusion: The shortage of teachers in basic subjects within medical colleges in Bangladesh significantly hampers the quality of education, leading to a lack of sufficient knowledge among students. This shortage may also have implications for their practical classes and training in the institutions. J Rang Med Col. March 2025; Vol.10, No.1: 57-62